An ecological and neurobiological perspective on the evolution of vocal learning - Brenowitz, Eliot A.; Beecher, Michael D. (Frontiers in Ecology and Evolution, 2023)
Vocal production learning (VPL) involves the use of auditory experience to guide the production of novel signals or to modify pre-existing signals. It allows animals to develop signals that are more complex and/or more flexible than innately developed signals. It has evolved rarely in vocal animals, widespread only in three avian and four mammalian taxa. The evolution of VPL was accompanied by innovations of the vocal motor neural circuitry. VPL is rare because of its various costs. Ecology, social spacing, and social fluidity can favor the evolution of VPL. It is striking that most taxa with VPL evolved in visually limited habitats, where sound is the only effective channel for communicating over distance from sender to receiver. Selective factors that favor the ability to produce complex and/or flexible signals would act predominantly on acoustic signals, and favor the evolution of VPL. Learning may be the only practical way to develop a signal complex enough to encode different types of information for assessment by receivers in animals that rely on acoustic communication, or to modify signals as local social factors dictate.